FORMULATION AND IN-VITRO CHARACTERIZATION OF FLUCONAZOLE TOPICAL GEL USING CARBOPOL POLYMER (Journal of Medical & Health Sciences Review, 2025)
The objective of this study was to develop and characterize a topical gel formulation of Fluconazole to provide a localized treatment for superficial fungal infections, thereby circumventing the side effects associated with its oral administration. Five gel formulations (F1-F5) were prepared using Carbopol 934P as the gelling agent in concentrations ranging from 0.5% to 1.5% w/w. The gels were evaluated for their physical appearance, homogeneity, pH, viscosity, spreadability, extrudability, drug content, and in-vitro drug release using a Franz diffusion cell. Drug-excipient compatibility was assessed using Fourier- Transform Infrared (FTIR) spectroscopy. All formulations were elegant, homogenous, and exhibited a translucent appearance. The pH values ranged from 6.3 to 6.8, which is compatible with skin pH. Viscosity increased with polymer concentration, ranging from 18,450 cP to 65,780 cP. Spreadability was inversely related to viscosity, with values between16.2 and 8.5 g.cm/sec. Drug content was uniform and high across all batches (97.2% - 99.4%). The in-vitro drug release study over 8 hours demonstrated a sustained release pattern, with cumulative drug release ranging from 71.5% to 91.3%. Formulation F3 (1.0% Carbopol) was identified as the optimal formulation, exhibiting a viscosity of 34,560 cP, spreadability of 12.1 g.cm/sec, and a sustained drug release of 86.7%. FTIR studies confirmed no interaction between Fluconazole and the excipients. A stable and effective topical gel of Fluconazole was successfully formulated. The 1.0% Carbopol 934P gel (F3) demonstrated the most desirable combination of physicochemical properties andsustained release profile, making it a promising candidate for the topical treatment of superficial fungal infections.